TINJAUAN PELAKSANAAN PERHITUNGAN, PEMOTONGAN DAN PENYETORAN PPH PASAL 4 AYAT 2 ATAS SEWA DAN BANGUNAN OLEH EVINCO MULIA CONSULTING - Rachel Gita Patricya (2022)
Final Income Tax Article 4 Paragraph 2 is a tax whose deduction is final, such as land and building rentals, for which the tax cannot be credited later. Regarding the data taken related to the preparation of this Final Project at PT Evinco Mulia Consulting, a company engaged in tax consulting services and has many clients regarding existing tax issues. One of the clients of PT Evinco Mulia Consulting is PT RLI, a company engaged in food and beverage trading in general. This final project was made with the aim of understanding the implementation of the calculation, withholding and reporting of the final income Tax PPh Article 4 Paragraph 2, PT RLI rents a lot of land and buildings as a place for trading. Tax consultant services for the withholding and reporting of the withholding tax, for calculation and mechanisme PT RLI submits everything to PT Evinco Mulia Consulting as a consulting service used by PT RLI. Evinco Mulia Consulting Frist asks for proof of invoice for the rental and the withholding tax will be calculated for the Article 4 Paragraph 2 income tax, then after that pays the amount into the state treasury through e-billing, and then reports in through the djp to get Proof of the tax deduction. So it can be conveyed that this Final Project report regarding the calculation, withholding, and reporting of Income Tax Article 4 Paragraph 2 by PT Evinco Mulia Consulting is timely and all in accordance with the existing laws and regulations.